Ageing and performance of warm mix asphalt pavements - Raab, Christiane; Camargo, Ingrid [UNESP]; Partl, Manfred N. (Elsevier B.V., 2017)
This paper presents results from investigating the ageing behaviour and performance of different warm mix asphalt (WMA) pavement mixtures also called energy reduced pavements. The mixtures were either prepared in the laboratory or taken directly from a mixing plant. The study compared the rutting and fatigue behaviours of unaged material in comparison to long term laboratory aged material. In order to conduct the long term ageing, a special laboratory ageing protocol with different heating, cooling and watering cycles had been developed. The investigation revealed a quite controversial rutting behavior which could not be explained with the available data. While most aged energy reduced pavements showed increased rutting for other mixtures, lower rut depths could be found. As opposed to this finding, fatigue and stiffness of all aged energy reduced pavement samples compared to unaged samples improved significantly. The overall results led to the conclusion that the ageing of energy reduced pavement simulated in the laboratory is not very critical regarding their mechanical performance. Therefore, it was confirmed that the application of this type of pavement provides a good solution for saving on CO2 emissions. Another advantage is that by using energy reduced pavements the road construction season can be significantly prolonged. (c) 2017 Periodical Offices of Chang'an University. Publishing services by Elsevier B.V. on behalf of Owner.
Keywords: Warm mix asphalt (WMA); CO2 emissions saving; Ageing; Long term performance; Rutting; Fatigue